EVALUASI PELAKSANAAN PROGRAM KELUARGA HARAPAN (PKH) TERHADAP KESEJAHTERAAN MASYARAKAT DI KECAMATAN MEDAN BARU KOTA MEDAN - Doli Tua Mulia Raja Panjaitan (JURNAL ILMIAH KOHESI, 2018)
Program Keluarga Harapan is a program that seeks to develop social protection system for the poorin Indonesia. This program provides cash assistance to RTSM with a note following the requirements relatedto improving the quality of human resources ie health and education. Layers of middle and low society manywho can not get education. This is because they have no cost to access education. Although many strategieshave been used to improve school access, the rate of school enrollment in Indonesia is still not optimal,especially for RTSM children. PKH in the field of education provides better opportunities for children inaccessing education. This is made possible with the assistance of this program, RTSM children who becomePKH participants will find it easier to access the available educational services.The purpose of this study is to describe how the process of implementing PKH and to analyze thecontent / content of policy and context / policy environment in the implementation of PKH in the field ofeducation as well as the field of health in the district of Medan Baru and how the results of PKH to the targetgroup in Medan Baru District. The method of research is quantitative by using the tools of survey method,sample and questionnaire as the main data collection tool. In data processing using SPSS application version20.0 for windows.Based on the research results, it can be seen that the companion always hold group meetingsregularly, updating the data, verification of commitment, and payment of assistance to PKH participants.From content factors and policy contexts, where the content of the policy consists of interests that affect, thetype of benefits, the degree of change to be achieved, program implementers and resources used. While thepolicy context factor consists of effectiveness, efficiency, adequacy, leveling, responsiveness, and accuracy.After conducting research, it can be concluded that the improvement of people's prosperity in Medan Barusub-district is influenced by effectiveness (x1), efficiency (x2), adequacy (x3), alignment (x4), responsiveness(x5), and accuracy (x6) 87, 1%. While the rest 12.9% explained by residual variable or other variables thatare not examined in this study such as supervision, leadership, and others